Coercive Control, Stalking, and Guns: Modeling Service Professionals' Perceived Risk of Potentially Fatal Intimate Partner Gun Violence. Issue 15 (August 2021) - Lynch, Kellie R.; Jackson, Dylan B.; Logan, TK
Intimate partner homicides often involve coercive control prior to the murder while stalking following separation has been associated with control within the relationship as well as with lethal violence. The goal of the present study was to investigate how rural and urban community professionals who encounter intimate partner violence (IPV) victims perceive potential risk factors for intimate partner homicide related to firearms and coercive control. Criminal justice and victim service professionals ( N = 133) from one urban and four rural communities participated in structured key informant interviews. A purposeful sampling procedure was employed to target professionals with expertise in domestic violence and/or firearms, followed by snowball sampling to maximize the response rate. The only risk factor that was directly associated with perceived risk of potentially fatal intimate partner gun violence was the perceived risk of an abuser threatening a victim with a gun. However, coercive control, separation, and stalking all mediated the relationship between the perceived risk of an abuser's access to a gun and the perceived risk of an abuser threatening the victim with a gun. These results highlight the importance of controlling behavior following separation for risk assessment and that participants in the present study were aware of the potentially dangerous ramifications of such nonphysically violent risk factors for the risk of injury or death by a firearm at the hands of an intimate partner.